Strategy and Online Marketing Based on E-Commerce (Shopee) to Micro Small and Medium Enterprises (MSMEs) In Kalisuren Village - Hestiolla, Thania; Hanifan, M. Zakie (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Based on the pre-survey that has been carried out previously, it is known that MSMEs in Kalisuren Village have experienced a decrease in sales turnover as a result of the Covid-19 pandemic conditions. This is the reason why it is important to implement a strategy to survive and adapt in the pandemic era. This socialization focused on counseling on online marketing strategies for MSMEs during the Covid-19 pandemic. The counseling provided was in the form of presentations on various online marketing strategies that can be applied in developing businesses in the midst of declining public purchasing power. The results of this socialization to the community are in the form of increasing MSME knowledge about various forms of online marketing strategies that can be applied to increase business in the pandemic era. The results of the evaluation also show that the majority of MSMEs think that the application of the strategies that have been taught can be done easily.